Dampak Kualitas Pelayanan Terhadap Pembelian Ulang Sparepart Mobil Di CV. XYZ Motor Bandung - Helmawati Helmawati; Tiris Sudrartono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The study aimed to find out the impact of service quality on the repurchase of car spare part at CV. Xyz Motor Bandung. The method used was a quantitative method with a descriptive type of research. The data obtained through questionnaire distributed to 91 people. In addition, the data analysis technique used was normality test using histogram graph and hypothesis test using t test. Based on the data obtained from the result of the study using SPSS V 23, it could be concluded that tcount > ttable (11.950 > 1.660) with a significant level of 0.00 < 0.05. Moreover, service quality was in a very good level with a percentage of 95.6% and the repurchase is in very good level with a percentage of 91.91%. Keywords: Service Quality, Repurchase